DETERMINAN KINERJA BISNIS UMKM SEKTOR KULINER DI KOTA DENPASAR - Rahmayanti, Putu Laksmita Dewi; Kawiana, I Gede Putu; Pratiwi, Komang Ary; Mashyuni, Ida Ayu; Saraswathi, Ida Ayu Anggawulan (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2023)
The degree of competition intensity will be a severe problem for a business including micro, small and medium enterprises (MSMEs), this occurs because the MSMEs has undergone changes characterized by rising competition in the business environment and increasing competitive pressures.  Multiple literary theories claim that robust competition engenders heightened performance.   Micro, Small, and Medium Enterprises (MSMEs) in Bali also include the principles and traditions of local wisdom in Bali.   In order to enhance corporate performance against fierce industry rivalry, it is imperative to employ strategies such as a service plan grounded in Tri Kaya Parisudha principles and a social media promotion strategy.   The study's population consisted of all owners/managers of micro, small, and medium enterprises (MSMEs) in the culinary sector in Denpasar. The sample size for this study was 95 respondents.   The sampling approach employed is non-probability sampling, specifically purposive sampling.   The data were analyzed utilizing the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach.   The results of hypothesis testing revealed that industry competition intensity, service strategy based on Tri Kaya Parisudha, and social media promotion strategy all had a positive and significant impact on business performance. Additionally, industry competition intensity was found to have a positive and significant influence on both the service strategy based on Tri Kaya Parisudha and the social media promotion strategy.